The hippocampus plays a selective role in the retrieval of detailed context memories - Wiltgen, Brian J (2010)
BACKGROUND: It is widely believed that the hippocampus plays a temporary role in the retrieval of episodic and contextual memories. Initial research indicated that damage to this structure produced amnesia for newly acquired memories but did not affect those formed in the distant past. A number of recent studies, however, have found that the hippocampus is required for the retrieval of episodic and contextual memories regardless of their age. These findings are currently the subject of intense debate and a satisfying resolution has yet to be identified. RESULTS: The current experiments address this issue by demonstrating that detailed memories always require the hippocampus while memories that lose precision become independent of this structure. First, we show that the dorsal hippocampus is preferentially activated by the retrieval of detailed context fear memories. We then establish a causal relationship between the hippocampus and detailed memories using a context generalization procedure. Mice that exhibit high levels of generalization to a novel environment show no memory loss when the hippocampus is subsequently inactivated. In contrast, mice that discriminate between contexts are significantly impaired by hippocampus inactivation. CONCLUSIONS: Our data suggest that detailed context memories always require the hippocampus (independent of their age) while memories that lose precision can be retrieved without this structure. These findings account for inconsistencies in the literature - memories of our distant past can be either lost or retained after hippocampus damage depending on their quality – and provide a new framework for understanding memory consolidation. HIGHLIGHTS: The retrieval of new context fear memories increases immediate early gene expression in the hippocampus. Immediate early gene expression decreases as memories age and become less precise. If memory is tested at a single retention interval, hippocampus inactivation selectively impairs the retrieval of precise context memories.